A biomimetic composite coating modified biological valve material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611426203.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]为了解决上述技术问题,本发明的目的是提供一种仿生复合涂层修饰的生物瓣膜材料及其制备方法和应用,以解决现有生物瓣膜性能较差的问题
1、本发明利用可逆加成-断裂链转移(RAFT)聚合技术合成含活性酯基团的两性离子共聚物p(MPC-co-NHS-MA),并通过化学键合的方式将其接枝到生物瓣膜表面,再将CD47衍生肽通过化学键合的方式连接到所得两性离子共聚物修饰的生物瓣膜上。本发明制得的经PMPC(两性离子共聚物)与CD47衍生肽协同修饰的生物瓣膜具有“被动防污-主动免疫调节”的双重功能,并表现出良好的稳定性和长效性,显著提升了瓣膜的生物相容性、抗炎、抗凝及抗钙化性能,具有广阔的临床应用前景。
Smart Images

Figure CN122912185A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of bioprosthetic valve material preparation technology, specifically to a bioprosthetic valve material modified with a biomimetic composite coating, its preparation method, and its application. Background Technology
[0002] The incidence and mortality rates of valvular heart disease (VHD) continue to rise rapidly with the accelerating aging of the population, becoming a major public health challenge in the global cardiovascular disease field. For patients where valve repair is not feasible, artificial valve replacement remains the primary treatment. Currently, the artificial heart valves widely used in clinical practice mainly include mechanical valves and bioprosthetic valves; among them, bioprosthetic valves are widely used in surgical and interventional valve replacement fields due to their superior hemodynamic performance and the fact that they do not require long-term anticoagulation therapy after surgery.
[0003] Most commercially available bioprosthetic valves use glutaraldehyde (GA) for chemical cross-linking to enhance their structural stability and reduce immunogenicity. However, the long-term durability of these valves is limited, with irreversible degeneration occurring within 10-15 years after implantation, eventually progressing to bioprosthetic valve failure (BVF). Studies have shown that BVF is not simply a physical wear-off or passive calcification process, but rather a complex pathological evolution and inflammatory response driven by the host's immune system, in which BVF plays a central role.
[0004] To extend the lifespan of bioprosthetic valves, surface functionalization has become an important strategy for improving their biocompatibility. However, existing technologies still face many challenges in achieving both long-term stability and active defense. Previous studies have shown that biomaterials modified by electrostatic adsorption or physical filling have poor stability and short shelf life in complex dynamic blood flow environments, making it difficult to meet the long-term service requirements of valves. Furthermore, existing surface modification strategies (such as polyethylene glycol conversion) mostly focus on constructing a hydration layer to inhibit non-specific protein adsorption. While such "passive isolation" strategies can slow down early protein deposition and thrombus formation, they cannot actively regulate the host immune response and have limited ability to intervene in key inflammatory processes such as macrophage polarization. Moreover, the limited number of active modification sites on the surface of GA-crosslinked bioprosthetic valves further increases the difficulty of constructing multifunctional modified systems. Therefore, how to develop a novel surface modification technology that can both block protein adsorption through "passive antifouling" and achieve "active immune regulation" to inhibit inflammatory responses while ensuring coating stability, thereby delaying the BVF process from the source and extending the service life of bioprosthetic valves, is a key scientific problem that urgently needs to be solved in the current bioprosthetic valve research field. Summary of the Invention
[0005] To address the aforementioned technical problems, the present invention aims to provide a biomimetic composite coating-modified biovalve material, its preparation method, and its application, thereby solving the problem of poor performance of existing biovalve materials.
[0006] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: a biomimetic composite coating modified biological valve material is provided, including a biological substrate, the surface of which is sequentially modified by chemical bonding with an amino-containing cationic polymer layer, an amphoteric copolymer layer and a CD47-derived peptide layer.
[0007] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, the residual amino groups on the surface of the biomimetic composite coating-modified biomimetic valve material are sealed by a compound containing active esters.
[0008] Furthermore, the active ester compound is N-acetic acid succinimide ester.
[0009] Furthermore, the biological substrate is decellularized bovine or porcine pericardium.
[0010] Furthermore, the amino-containing cationic polymer is branched polyethyleneimine.
[0011] Furthermore, the molecular weight of branched polyethyleneimine is 300 g / mol to 1,000,000 g / mol.
[0012] Furthermore, the molecular weight of branched polyethyleneimine is 25,000 g / mol.
[0013] Furthermore, the zwitterionic copolymer is prepared by dissolving the zwitterionic monomer, the active ester monomer, the initiator and the chain transfer agent in a solvent and performing RAFT polymerization.
[0014] Furthermore, the zwitterionic monomer is 2-methacryloyloxyethyl phosphocholine; the active ester monomer is N-hydroxysuccinimide methacrylate; the initiator is azobisisobutyronitrile; and the chain transfer agent is 4-cyano-4-(thiobenzoyl)valerate.
[0015] Furthermore, the molar ratio of zwitterionic monomer, active ester monomer, initiator and chain transfer agent is (10-200):(1-40):(0.1-0.4):1.
[0016] Furthermore, the molar ratio of zwitterionic monomer, active ester monomer, initiator and chain transfer agent is 67.8:10:0.349:1.
[0017] Furthermore, the solvent is methanol.
[0018] Furthermore, polymerization was carried out in an anaerobic environment at 25℃-65℃ with stirring for 24h-72h.
[0019] Furthermore, polymerization was carried out in an anaerobic environment at 65 °C with stirring for 24 h.
[0020] Furthermore, the amino acid sequence of the CD47-derived peptide is GNYTCEVTELTREGETIIELK-NH2.
[0021] Furthermore, the CD47-derived peptide is a synthetic peptide containing a binding site for the signal regulatory protein α, with the amino acid sequence GNYTCEVTELTREGETIIELK-NH2.
[0022] This invention also provides a method for preparing the above-mentioned biomimetic composite coating modified biological valve material, which includes the following steps: (1) The biological substrate is pretreated to obtain a pretreated biological substrate; (2) The pretreated biological substrate obtained in step (1) is immersed in an amino-containing cationic polymer solution and an activator is added to carry out amination modification to obtain an amino-containing cationic polymer layer. (3) Immerse in zwitterionic copolymer solution and perform covalent grafting to obtain zwitterionic copolymer layer; (4) Immerse in CD47-derived peptide solution for functionalization coupling to obtain CD47-derived peptide layer; (5) Immerse in a solution containing active ester compounds and perform surface residual active amino sealing treatment to obtain a biomimetic composite coating modified biovalve material.
[0023] Furthermore, in step (1), the biological substrate is bovine pericardium or porcine pericardium.
[0024] Furthermore, in step (1), the biological substrate is decellularized and cross-linked with glutaraldehyde to complete the pretreatment.
[0025] Furthermore, sodium dodecyl sulfate solution was used for decellularization.
[0026] Furthermore, during glutaraldehyde crosslinking, the concentration of the glutaraldehyde solution is 0.05 wt%-8 wt%.
[0027] Furthermore, in step (2), the activator is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide.
[0028] Furthermore, in step (2), the molar ratio of the activator to the theoretical amino group on the surface of the biological substrate is 0.15:1.
[0029] Furthermore, in step (2), the concentration of the amino-containing cationic polymer solution is 1 mg / mL to 15 mg / mL.
[0030] Furthermore, in step (2), the amination modification is carried out at pH 4-8 and 4℃-37℃ for 2h-48h.
[0031] Furthermore, in step (3), the concentration of the zwitterionic copolymer solution is 0.01 mg / mL to 50 mg / mL.
[0032] Furthermore, in step (3), covalent grafting is performed at pH 4-8 and 4℃-37℃ for 2h-48h.
[0033] Furthermore, in step (3), after obtaining the zwitterionic copolymer layer, steps (2) and (3) are repeated, and then step (4) is performed.
[0034] Furthermore, in step (4), the concentration of the CD47-derived peptide solution is 0.01 mg / mL to 100 mg / mL.
[0035] Furthermore, in step (4), functionalization coupling is performed at pH 4-8 and 4℃-37℃ for 2h-48h.
[0036] Furthermore, in step (5), the active ester compound is acetic acid-N-succinimide ester.
[0037] Furthermore, in step (5), the concentration of the solution containing the active ester compound is 0.1 mg / mL to 10 mg / mL.
[0038] Furthermore, in step (5), the surface residual active amino groups are sealed for 0.5 h to 48 h under conditions of pH 4-8, 4℃-37℃ and shaking.
[0039] This invention also provides the application of the above-mentioned biomimetic composite coating modified biological valve material in the preparation of biological valves.
[0040] The present invention has the following beneficial effects: 1. This invention utilizes reversible addition-fragmentation chain transfer (RAFT) polymerization technology to synthesize a zwitterionic copolymer p(MPC-co-NHS-MA) containing active ester groups, and then grafts it onto the surface of a bioprosthetic valve through chemical bonding. A CD47-derived peptide is then chemically bonded to the bioprosthetic valve modified with the resulting zwitterionic copolymer. The bioprosthetic valve prepared by this invention, synergistically modified with PMPC (zwitterionic copolymer) and CD47-derived peptide, possesses dual functions of "passive antifouling and active immune regulation," exhibiting good stability and long-lasting effects. It significantly improves the valve's biocompatibility, anti-inflammatory, anticoagulant, and anti-calcification properties, and has broad clinical application prospects.
[0041] 2. This invention constructs a biomimetic composite coating through chemical bonding. Compared with traditional modification methods that rely on electrostatic adsorption or physical filling, the prepared coating has excellent stability and long-lasting effect, which can improve the long-term anti-inflammatory, anticoagulant and anti-calcification properties of valves and significantly extend their service life.
[0042] 3. This invention introduces zwitterionic copolymers onto the surface of bioprosthetic valve materials, which can form a stable hydration layer on the surface, effectively reducing non-specific protein adsorption and reducing the risk of thrombosis and coagulation from the source.
[0043] 4. This invention introduces CD47-derived peptides onto the surface of bioprosthetic valve materials, which can actively regulate the host's immune rejection response through the CD47-SIRPα signaling pathway, reduce inflammatory cell infiltration, and significantly improve the anti-inflammatory performance of bioprosthetic valves.
[0044] 5. The bioprosthetic valve modification method of the present invention can effectively block the residual aldehyde groups on the glutaraldehyde cross-linked bioprosthetic valve, thereby effectively reducing the potential calcification risk and biotoxicity of the bioprosthetic valve. Attached Figure Description
[0045] Figure 1 The NMR spectrum of the zwitterionic copolymer is shown in the form of 1H NMR. Figure 2 Scanning electron microscope images of the bioprosthetic valve materials prepared in Comparative Example 1 and Comparative Example 2. Figure 3 The energy spectrum distribution of phosphorus in the bio-valve materials prepared in Comparative Example 1 and Comparative Example 2 is shown. Figure 4 The images show the in vitro collagenase degradation results of the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1. Figure 5 The graph shows the cytotoxicity results of the extracts of the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1. Figure 6 Fluorescent staining images of endothelial cell adhesion of bioprosthetic valve materials prepared in Example 1 and Comparative Example 1; Figure 7 This is a statistical chart showing the number of cells adhering to the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1. Figure 8 These are fluorescent staining images of the competitive adhesion of cells to the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1. Figure 9 This is a statistical chart showing the number of cells competitively adhering to the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1. Figure 10 The images show the hemolysis test results of the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1. Figure 11 Statistics on the hemolysis rate of the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1; Figure 12 The graphs show the anticoagulant properties and blood compatibility of the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1. Figure 13 The absorbance values are the anticoagulant properties and blood compatibility test results of the bioprosthetic valve materials prepared in Example 1 and Comparative Example 1. Figure 14 Immunofluorescence staining images of the bioprosthetic valve materials prepared in Example 1, Comparative Example 1, and Comparative Example 2; Figure 15 The images show the ELISA results of the bioprosthetic valve materials prepared in Example 1 and Comparative Example 2. Detailed Implementation
[0046] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used that do not specify the manufacturer are all commercially available conventional products.
[0047] Example 1: A biomimetic composite coating modified bio-valve material, the preparation method of which includes the following steps in sequence: (1) Remove connective tissue from the biological substrate (fresh porcine pericardium) and clean it thoroughly with physiological saline. Then soak it in sodium dodecyl sulfate (SDS) solution (5 wt%) and shake for 48 h for decellularization. Then soak it in glutaraldehyde solution (1 wt%) and shake for 48 h. Finally, wash it thoroughly with physiological saline. (2) Immerse in a cationic polymer solution containing amino groups (branched polyethyleneimine, 10 mg / mL, molecular weight 25000 g / mol), and add EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and NHS (N-hydroxysuccinimide) with 0.15 times the theoretical molar number of amino groups on the surface of the biological substrate. Amide modification is carried out at pH 5.5 and 37℃ for 12 h. After removal, it is thoroughly washed with physiological saline. (3) Immerse in zwitterionic copolymer solution (5 mg / mL) and covalently graft for 4 h at pH 7, 37℃ and shaking conditions. After removal, rinse thoroughly with physiological saline. (4) Immerse in CD47-derived peptide solution (1 mg / mL) and functionalize and couple for 12 h at pH 7, 37°C and shaking conditions. After removal, rinse thoroughly with physiological saline. (5) Immerse in a solution containing active ester compound (acetic acid-N-succinimide ester solution, 5 mg / mL), and perform surface residual active amino sealing treatment for 5 h under pH 7, 37 ℃ and shaking conditions to obtain biomimetic composite coating modified biological valve material (denoted as PMPC-CD47-BP).
[0048] The zwitterionic copolymer was prepared by the following method: zwitterionic monomers (2-methacryloyloxyethyl phosphocholine, MPC, 5 g, 16.95 mmol), active ester monomers (N-hydroxysuccinimide methacrylate, NHS-MA, 0.458 g, 2.5 mmol), initiator (azobisisobutyronitrile, AIBN, 14.31 mg, 0.087 mmol), and chain transfer agent (4-cyano-4-(thiobenzoylthio)valeric acid, 69.85 mg, 0.25 mmol) were dissolved in a solvent (methanol, 15 mL). Nitrogen gas was introduced to remove oxygen, and the mixture was stirred in an oil bath at 65°C for 24 h to undergo RAFT (reversible addition-fragmentation chain transfer) polymerization. After the reaction was complete, the initial product was added dropwise to anhydrous diethyl ether to precipitate the product. The target product was collected and dried under vacuum to obtain 3.65 g of the zwitterionic copolymer (yield 66.9%). %, denoted as p(MPC-co-NHS-MA)).
[0049] The reaction formula is:
[0050] Example 2: A biomimetic composite coating modified bio-valve material, the preparation method of which includes the following steps in sequence: (1) Remove connective tissue from the biological substrate (fresh porcine pericardium) and clean it. Wash it with physiological saline, then soak it in sodium dodecyl sulfate (SDS) solution (5 wt%) and shake it for 48 h to remove cells. Then soak it in glutaraldehyde solution (1 wt%) and shake it for 48 h. Finally, wash it thoroughly with physiological saline. (2) The pretreated biological substrate obtained in step (1) was immersed in a cationic polymer solution containing amino groups (branched polyethyleneimine, 10 mg / mL, molecular weight 25000 g / mol), and EDC and NHS with a theoretical amino molar number of 0.15 times were added to the surface of the biological substrate. The substrate was aminated and modified for 2 h at pH 5.5 and 37°C. After removal, it was thoroughly washed with physiological saline. (3) Immerse in zwitterionic copolymer solution (5 mg / mL) and covalently graft for 4 h at pH 7, 37℃ and shaking conditions. After removal, rinse thoroughly with physiological saline. (4) Immerse in a cationic polymer solution containing amino (branched polyethyleneimine, 10 mg / mL, molecular weight 25000 g / mol), and aminate for 2 h at pH 5.5 and 37 °C. After removal, rinse thoroughly with physiological saline. (5) Immerse in zwitterionic copolymer solution (5 mg / mL) and covalently graft for 4 h at pH 7, 37°C and shaking conditions. After removal, rinse thoroughly with physiological saline. (6) Immerse in CD47-derived peptide solution (1 mg / mL) and functionalize and couple for 12 h at pH 7, 37°C and shaking conditions. After removal, rinse thoroughly with physiological saline. (7) Immerse the biomimetic composite coating modified biological valve material in a solution containing active ester compound (acetic acid-N-succinimide ester solution, 5 mg / mL) and perform surface residual active amino sealing treatment for 5 h under pH 7, 37℃ and shaking conditions to obtain biomimetic composite coating modified biological valve material.
[0051] The preparation method of the zwitterionic copolymer is the same as in Example 1.
[0052] Example 3: A biomimetic composite coating modified bio-valve material, the preparation method of which includes the following steps in sequence: (1) Remove connective tissue from the biological substrate (fresh porcine pericardium) and clean it thoroughly with physiological saline. Then soak it in sodium dodecyl sulfate (SDS) solution (0.05 wt%) and shake for 48 h to remove cells. Then soak it in glutaraldehyde solution (0.05 wt%) and shake for 48 h. Finally, wash it thoroughly with physiological saline. (2) The pretreated biological substrate obtained in step (1) was immersed in a cationic polymer solution containing amino (branched polyethyleneimine, 1 mg / mL, molecular weight 300 g / mol), and EDC and NHS with a theoretical amino molar number of 0.15 times were added to the surface of the biological substrate. The substrate was aminated and modified for 48 h at pH 4 and 4℃. After removal, it was thoroughly washed with physiological saline. (3) Immerse in zwitterionic copolymer solution (0.01 mg / mL) and covalently graft for 48 h at pH 4, 4 °C and shaking conditions. After removal, rinse thoroughly with physiological saline. (4) Immerse in CD47-derived peptide solution (1 mg / mL) and functionalize and couple for 48 h at pH 4, 4 °C and with shaking. After removal, rinse thoroughly with physiological saline. (5) Immerse the biomimetic composite coating modified biological valve material in a solution containing active ester compound (acetic acid-N-succinimide ester solution, 0.1 mg / mL) and perform surface residual active amino sealing treatment for 48 h under pH 4, 4℃ and shaking conditions to obtain biomimetic composite coating modified biological valve material.
[0053] The zwitterionic copolymer was prepared by the following method: zwitterionic monomers (2-methacryloyloxyethyl phosphocholine, MPC, 0.741 g, 2.51 mmol), active ester monomers (N-hydroxysuccinimide methacrylate, NHS-MA, 46.0 mg, 0.251 mmol), initiator (azobisisobutyronitrile, AIBN, 4.16 mg, 0.0254 mmol), and chain transfer agent (4-cyano-4-(thiobenzoylthio)valerate, 70.02 mg, 0.251 mmol) were dissolved in a solvent (methanol, 15 mL), nitrogen gas was introduced to remove oxygen, and the mixture was stirred in an oil bath at 65 °C for RAFT (reversible addition-fragmentation chain transfer) polymerization for 24 h. After the reaction was completed, the initial product was added dropwise to anhydrous diethyl ether to precipitate the product. The target product was collected and dried under vacuum to obtain 0.528 g of zwitterionic copolymer (yield 67.1%).
[0054] Example 4: A biomimetic composite coating modified bio-valve material, the preparation method of which includes the following steps in sequence: (1) Remove connective tissue from the biological substrate (fresh porcine pericardium) and clean it. Wash it with physiological saline, then soak it in sodium dodecyl sulfate (SDS) solution (8 wt%) and shake it for 48 h to remove cells. Then soak it in glutaraldehyde solution (8 wt%) and shake it for 48 h. Finally, wash it thoroughly with physiological saline. (2) The pretreated biological substrate obtained in step (1) was immersed in a cationic polymer solution containing amino groups (branched polyethyleneimine, 15 mg / mL, molecular weight 1,000,000 g / mol), and EDC and NHS with a theoretical amino molar number of 0.15 times were added to the surface of the biological substrate. The substrate was aminated and modified for 2 h at pH 8 and 20°C. After removal, it was thoroughly washed with physiological saline. (3) Immerse in zwitterionic copolymer solution (50 mg / mL) and covalently graft for 2 h at pH 8, 20℃ and shaking conditions. After removal, rinse thoroughly with physiological saline. (4) Immerse in CD47-derived peptide solution (1 mg / mL) and functionalize and couple for 2 h at pH 8, 20°C and shaking conditions. After removal, rinse thoroughly with physiological saline. (5) Immerse the biomimetic composite coating modified biological valve material in a solution containing active ester compound (acetic acid-N-succinimide ester solution, 10 mg / mL) and perform surface residual active amino sealing treatment for 0.5 h under pH 8, 20 ℃ and shaking conditions to obtain biomimetic composite coating modified biological valve material.
[0055] The zwitterionic copolymer was prepared by the following method: zwitterionic monomers (2-methacryloyloxyethyl phosphocholine, MPC, 14.72 g, 49.90 mmol), active ester monomers (N-hydroxysuccinimide methacrylate, NHS-MA, 1.826 g, 9.97 mmol), initiator (azobisisobutyronitrile, AIBN, 16.3 mg, 0.099 mmol), and chain transfer agent (4-cyano-4-(thiobenzoylthio)valerate, 69.7 mg, 0.249 mmol) were dissolved in a solvent (methanol, 15 mL), and nitrogen gas was introduced to remove oxygen. The mixture was stirred in an oil bath at 65 °C and subjected to RAFT (reversible addition-fragmentation chain transfer) polymerization for 24 h. After the reaction was completed, the initial product was added dropwise to anhydrous diethyl ether to precipitate the product. The target product was collected and dried under vacuum to obtain 11.1 g of zwitterionic copolymer (yield 67.1%).
[0056] Comparative Example 1: A biological valve material, the preparation method of which includes the following steps in sequence: Only step (1) of Example 1 is included, and the product obtained is glutaraldehyde cross-linked biovalve material (denoted as Glut-BP).
[0057] Comparative Example 2: A biological valve material, the preparation method of which includes the following steps in sequence: The product obtained is a zwitterionic copolymer modified biovalve material (denoted as PMPC-BP), which includes only steps (1) to (3) in Example 1.
[0058] Test case The biomimetic composite coating-modified biomimetic valve materials prepared in Examples 1-4 have basically the same physicochemical properties. The following experiment is conducted using Example 1 as an example.
[0059] All experimental data are expressed as mean ± standard deviation. For comparisons between two groups, Student's t-test was used to determine statistical significance; for comparisons involving multiple groups, Bonferroni-corrected one-way ANOVA was used to determine statistical significance. P < 0.05 indicated a statistically significant difference. This indicates that P < 0.05. This indicates that P < 0.01. This indicates that P < 0.001. P < 0.0001 indicates that the difference is not statistically significant. ns indicates that the difference is not statistically significant.
[0060] I. Proton NMR Spectroscopy The zwitterionic copolymer p(PMPC-co-NHS-MA) prepared in Example 1 was dissolved in deuterated methanol, and its 1H NMR spectrum was analyzed. The results are shown in [Figure 1]. Figure 1 .
[0061] Depend on Figure 1 It can be seen that characteristic signals of quaternary ammonium salt methyl protons appear near δ3.1-3.3 ppm; multiple sets of methylene proton signals appear in the range of δ3.5-4.5 ppm. At the same time, characteristic signals of methylene protons on the succinimide ring can be observed at δ2.7-2.9 ppm; and proton signals related to the polymethacrylate backbone appear in the range of δ0.8-2.2 ppm, indicating that the methacrylate monomers have polymerized and formed the polymer backbone.
[0062] The above results demonstrate that this invention successfully prepared a p(MPC-co-NHS-MA) copolymer containing both a zwitterionic structure of phosphocholine and an active NHS ester structure via RAFT polymerization. The phosphocholine groups in this copolymer impart hydrophilic and antifouling properties to the surface of the bioprosthetic valve material, while the NHS active ester groups can react with amino groups on the material surface or in the cationic polymer layer, providing a structural basis for the stable grafting of the zwitterionic copolymer onto the bioprosthetic valve surface and subsequent coupling with CD47-derived peptides.
[0063] II. Scanning Electron Microscope The glutaraldehyde cross-linked biovalve material (Glut-BP) prepared in Comparative Example 1 and the zwitterionic copolymer modified biovalve material (PMPC-BP) prepared in Comparative Example 2 were observed by scanning electron microscopy. The results are shown in the figure. Figure 2 .
[0064] Depend on Figure 2 It can be seen that the surface of Glut-BP prepared in Comparative Example 1 has obvious network pore structure and exposed collagen fiber structure, and the surface is relatively rough. In contrast, the surface of PMPC-BP prepared in Comparative Example 2 shows a relatively continuous and dense coverage morphology, with reduced pore structure and reduced collagen exposure.
[0065] The above results indicate that the zwitterionic copolymer can uniformly cover the surface of the glutaraldehyde-crosslinked bioprosthetic valve material, forming a continuous surface modification layer. This surface morphology change demonstrates that the zwitterionic copolymer layer has been successfully constructed, which is beneficial for reducing direct exposure of the collagen matrix and minimizing non-specific adhesion of proteins and cells.
[0066] III. Energy Spectrum Distribution of Phosphorus The surface elemental distribution of Glut-BP prepared in Comparative Example 1 and PMPC-BP prepared in Comparative Example 2 was analyzed using energy-dispersive X-ray spectroscopy (EDS). The results are shown in the figure. Figure 3 .
[0067] Depend on Figure 3 It can be seen that, compared with the Glut-BP prepared in Comparative Example 1, the PMPC-BP prepared in Comparative Example 2 exhibits a significant phosphorus (P) element signal on its surface, and the P element is relatively uniformly distributed on the material surface. Since the MPC structural unit contains phosphocholine groups, the appearance of the P element signal indicates that the zwitterionic copolymer has been successfully introduced into the surface of the bio-valve material.
[0068] The above results further demonstrate that the zwitterionic copolymer described in this invention can be effectively grafted onto the surface of glutaraldehyde-crosslinked biomolecular valve material, providing a basis for the subsequent construction of PMPC-CD47 biomimetic composite coating.
[0069] IV. In vitro collagenase degradation The biomimetic composite coating modified biomolecular valve material (PMPC-CD47-BP) prepared in Example 1 and Glut-BP prepared in Comparative Example 1 were lyophilized and weighed (W0). They were then placed in collagenase solution for in vitro degradation experiments. After the reaction, they were lyophilized again and weighed (W1) to detect the material mass loss rate. The formula for calculating the mass loss rate is as follows: Mass loss rate = (W0 - W1) / W0 × 100%.
[0070] Depend on Figure 4 It can be seen that the Glut-BP prepared in Comparative Example 1 had a high mass loss rate after collagenase treatment, while the PMPC-CD47-BP prepared in Example 1 had a significantly lower mass loss rate, and the difference between the two groups was statistically significant (P<0.01).
[0071] The above results demonstrate that by constructing a PMPC-CD47 biomimetic composite coating on the surface of biomimetic valve materials, this invention can effectively reduce the degradation effect of collagenase on the collagen matrix, and improve the material's resistance to enzyme degradation and structural stability.
[0072] V. Cytotoxicity of Extract PMPC-CD47-BP prepared in Example 1 and Glut-BP prepared in Comparative Example 1 were sterilized by ultraviolet irradiation and then placed in 1 mL of DMEM medium containing 5% fetal bovine serum, respectively, and incubated at 37°C for 72 h. After incubation, the supernatant was collected as the extraction solution for the corresponding material. The obtained extraction solutions were co-cultured with endothelial cells for 24 h and 48 h, respectively. Subsequently, the absorbance (OD value) of each group at a wavelength of 450 nm was measured, and the relative cell viability was calculated. The results are shown in [Figure number missing]. Figure 5 Relative cell viability is calculated using the following formula: Relative cell viability (%) = OD 实施例组 / OD mean 空白对照组 ×100% or relative cell viability (%) = OD 对比例组 / OD mean 空白对照组 ×100%.
[0073] Depend on Figure 5 It was found that after treatment with the Glut-BP extract prepared in Comparative Example 1 for 24 h, the relative cell viability decreased significantly; after treatment for 48 h, the relative cell viability decreased further. In contrast, after treatment with the PMPC-CD47-BP extract prepared in Example 1 for 24 h and 48 h, the relative cell viability remained at a high level, significantly higher than that of Glut-BP prepared in Comparative Example 1, and the difference was statistically significant (P < 0.0001).
[0074] The above results demonstrate that the PMPC-CD47 biomimetic composite coating constructed on the surface of the biomimetic valve material in this invention has good cell compatibility and biosafety.
[0075] VI. Endothelial cell adhesion PMPC-CD47-BP prepared in Example 1 and Glut-BP prepared in Comparative Example 1 were co-cultured with endothelial cells for 24 h and 48 h, respectively. The adhesion of endothelial cells to the material surface was observed by fluorescent staining, and the number of adherent cells was statistically analyzed. The results are shown in [Figure 1]. Figures 6-7 .
[0076] Depend on Figure 6 It can be seen that only a small number of endothelial cells adhered to the Glut-BP surface prepared in Comparative Example 1 after 24 h and 48 h of culture; while the PMPC-CD47-BP surface prepared in Example 1 showed more endothelial cells adhering after 24 h of culture, and the number of cells further increased after 48 h of culture.
[0077] Depend on Figure 7 It can be seen that at both 24 h and 48 h time points, the number of endothelial cells on the surface of PMPC-CD47-BP prepared in Example 1 was significantly higher than that of Glut-BP prepared in Comparative Example 1, and the difference was statistically significant.
[0078] The above results indicate that by constructing a PMPC-CD47 biomimetic composite coating on the surface of bioprosthetic valve materials, this invention can significantly improve the adhesion and growth performance of endothelial cells on the material surface, enhance the cell compatibility and endothelialization potential of the material, and provide a basis for improving the blood compatibility and long-term stability of bioprosthetic valve materials after implantation.
[0079] VII. Competitive Adhesion The PMPC-CD47-BP prepared in Example 1 and the Glut-BP prepared in Comparative Example 1 were used to conduct competitive adhesion assays with HUVECs endothelial cells and RAW 264.7 macrophages, respectively. The culture media were HUVECs-specific medium and RAW264.7-specific medium, respectively. A blank (without material) was used as a control. The cells were grouped as blank, Glut-BP, and PMPC-CD47-BP. The adhesion of the two cell types to different material surfaces was observed by fluorescent staining, and the number of adherent cells was statistically analyzed. The results are shown in […]. Figures 8-9 .
[0080] Depend on Figure 8 As shown, the first and second columns are fluorescence images of endothelial cells (HUVECs) and macrophages (RAW264.7) on the material surface, respectively. The third column is an overlay image of the two, used to characterize the competitive adhesion of HUVECs and RAW264.7 to the same material surface. Green fluorescence represents HUVECs, and red fluorescence represents RAW264.7. In the blank control group, a large number of green and red fluorescent cells were observed. Both types of cells were abundant in the overlay image, indicating that both HUVECs and RAW264.7 could adhere to the blank control surface. On the Glut-BP surface prepared in Comparative Example 1, only a small number of HUVECs and RAW264.7 were observed, and both green and red fluorescence were scarce in the overlay image, indicating that the glutaraldehyde-crosslinked material alone is not conducive to the adhesion of these two cell types. In contrast, the PMPC-CD47-BP surface prepared in Example 1 showed a greater number of green fluorescently labeled HUVECs, while the number of red fluorescently labeled RAW 264.7 was relatively small. The overlay image further showed that under conditions of coexistence and competitive adhesion between HUVECs and RAW 264.7, the PMPC-CD47-BP surface was mainly occupied by HUVECs, while the adhesion of RAW 264.7 was relatively suppressed. These results indicate that PMPC-CD47-BP is beneficial for the adhesion of HUVECs under competitive adhesion conditions, while reducing the adhesion of RAW 264.7, thus promoting endothelialization of the material surface.
[0081] Depend on Figure 9It can be seen that the number of HUVECs adhering in the PMPC-CD47-BP group was significantly higher than that in RAW 264.7, and the difference was statistically significant (P<0.01); while there was no statistically significant difference in the number of HUVECs adhering to RAW 264.7 in the blank group and Glut-BP group.
[0082] The above results indicate that by constructing a PMPC-CD47 biomimetic composite coating on the surface of the biomimetic valve material, the present invention can promote endothelial cell adhesion and reduce macrophage relative adhesion in a competitive cell adhesion environment, which is beneficial to improving the endothelialization potential and anti-inflammatory immunocompatibility of the material.
[0083] 8. Hemolysis test PMPC-CD47-BP prepared in Example 1, Glut-BP prepared in Comparative Example 1, physiological saline, and Triton X-100 were co-incubated with rabbit erythrocyte suspensions, respectively. The groups were designated as Triton X-100, physiological saline, Glut-BP, and PMPC-CD47-BP, with the physiological saline group serving as the negative control and the Triton X-100 group as the positive control. After incubation, the samples from each group were centrifuged, and the color of the supernatant was observed and recorded. Subsequently, the absorbance (OD value) of each group at a wavelength of 450 nm was measured, and the hemolysis rate was calculated. The results are shown in […]. Figures 10-11 The hemolysis rate is calculated using the following formula: Hemolysis rate (%) = (OD) / (OD) 实施例组 -OD 生理盐水组 ) / (OD TritonX-100组 -OD 生理盐水组 ) × 100% or hemolysis rate (%) = (OD 对比例组 -OD 生理盐水组 ) / (OD TritonX-100组 -OD 生理盐水组 )×100%.
[0084] Depend on Figure 10 It can be seen that the supernatant of the Triton X-100 group was distinctly red, indicating that the red blood cells had undergone significant rupture; the supernatant of the saline group was basically clear, indicating that no significant hemolysis had occurred. The supernatants of the Glut-BP group and the PMPC-CD47-BP group did not show obvious redness, and the supernatant of the PMPC-CD47-BP group was clearer.
[0085] Depend on Figure 11 It can be seen that the hemolysis rate in the Triton X-100 group was close to 100%, while the hemolysis rate in the saline group was close to 0. The hemolysis rate in the Glut-BP group was lower, while the hemolysis rate in the PMPC-CD47-BP group was further reduced, and the difference was statistically significant compared with the Glut-BP group (P < 0.001).
[0086] The above results indicate that by constructing a PMPC-CD47 biomimetic composite coating on the surface of the biomimetic valve material, the present invention can reduce the hemolytic reaction caused by the material coming into contact with red blood cells and improve the blood compatibility of the material.
[0087] IX. Anticoagulant properties and blood compatibility PMPC-CD47-BP prepared in Example 1 and Glut-BP prepared in Comparative Example 1 were respectively contacted with recalcified whole blood, and grouped as Glut-BP and PMPC-CD47-BP. After the reaction, the blood residue on the material surface was observed, and the absorbance at 405 nm was measured. The results are shown in the figure. Figures 12-13 .
[0088] Depend on Figure 12 It can be seen that the surface of Glut-BP prepared in Comparative Example 1 is obviously red, indicating that there are more blood components and coagulation deposits on its surface; in contrast, the surface color of PMPC-CD47-BP prepared in Example 1 is significantly lighter, and the blood residue and coagulation deposits are reduced.
[0089] Depend on Figure 13 It can be seen that the absorbance value of the Glut-BP group at 405 nm is higher, while the absorbance value of the PMPC-CD47-BP group is significantly lower, and the difference between the two groups is statistically significant (P<0.0001).
[0090] The above results indicate that by constructing a PMPC-CD47 biomimetic composite coating on the surface of the biomimetic valve material, the present invention can reduce the deposition of blood components and coagulation reaction caused by recalcified whole blood coming into contact with the material, thereby improving the anticoagulation performance and blood compatibility of the material.
[0091] 10. Immunofluorescence staining PMPC-CD47-BP prepared in Example 1, Glut-BP prepared in Comparative Example 1, and PMPC-BP prepared in Comparative Example 2 were co-cultured with RAW 264.7 macrophages for 48 h using RAW 264.7 cell-specific culture medium. A blank culture system without the materials was used as a control group. The cells were divided into blank, Glut-BP, PMPC-BP, and PMPC-CD47-BP groups. After culture, immunofluorescence staining was performed on the macrophage pro-inflammatory marker iNOS (inducible nitric oxide synthase), and DAPI (4',6-diamidinyl-2-phenylindole) was used to stain the cell nuclei. Subsequently, the iNOS fluorescence images and DAPI fluorescence images were merged to show the spatial distribution relationship of the two fluorescence signals. The results are shown in [Figure 1]. Figure 14 .
[0092] Depend on Figure 14As shown, the first row is an iNOS immunofluorescence staining image, where red fluorescence represents iNOS expression; the second row is a DAPI staining image, where blue fluorescence represents cell nuclei, used to show the distribution of macrophages in each group; the third row is a combined image of iNOS and DAPI fluorescence signals, used to characterize the spatial correspondence between iNOS signals and macrophages. In the Glut-BP group, the iNOS red fluorescence signal was stronger, and strong red fluorescence was observed around the blue cell nuclei in the combined image, indicating that the glutaraldehyde cross-linking material alone can induce a significant pro-inflammatory activation response in macrophages. Compared with the Glut-BP group, the iNOS fluorescence signal in the PMPC-BP group was weakened, and the intensity of red fluorescence around the cell nuclei in the combined image was also correspondingly reduced, indicating that the zwitterionic copolymer layer can reduce iNOS expression in macrophages to a certain extent and weaken the pro-inflammatory activation of macrophages. In the PMPC-CD47-BP group, the iNOS fluorescence signal was further reduced, and only a relatively weak red fluorescence signal was observed around the blue cell nuclei in the merged image, suggesting that the PMPC-CD47 biomimetic composite coating can further reduce the expression of the macrophage pro-inflammatory marker iNOS.
[0093] Furthermore, clear blue cell nuclei were observed in all DAPI-stained images, indicating that the cell nuclei of macrophages in each group were effectively labeled. In the merged images, the iNOS fluorescence signal was mainly distributed around the blue cell nuclei, indicating that the detected iNOS signal corresponds to macrophages. By comparing the intensity of red fluorescence around the cell nuclei in the merged images of each group, the influence of different materials on the degree of pro-inflammatory activation of macrophages can be further reflected.
[0094] The above results indicate that by constructing a PMPC-CD47 biomimetic composite coating on the surface of biomimetic valve materials, this invention can reduce macrophage iNOS expression and weaken macrophage pro-inflammatory activation responses, thereby improving the anti-inflammatory properties and immunocompatibility of biomimetic valve materials.
[0095] XI. ELISA PMPC-CD47-BP prepared in Example 1 and PMPC-BP prepared in Comparative Example 2 were co-cultured with RAW 264.7 macrophages for 48 h in RAW 264.7 cell-specific medium. A blank control (containing no material) was used. Cells were grouped as blank, Glut-BP, PMPC-BP, and PMPC-CD47-BP. Cell culture supernatants were collected, and the expression level of TNF-α (tumor necrosis factor-α) in the supernatant was detected by ELISA (enzyme-linked immunosorbent assay). Results are shown below. Figure 15 .
[0096] Depend on Figure 15The results showed that the TNF-α expression level in the PMPC-BP group was higher than that in the Control group, and the difference was statistically significant (P < 0.01), indicating that the zwitterionic copolymer modification alone could still induce a certain degree of pro-inflammatory factor release. In contrast, the TNF-α expression level in the PMPC-CD47-BP group was lower than that in the control group, and the difference was statistically significant (P < 0.05). Meanwhile, there was no statistically significant difference between the PMPC-CD47-BP group and the control group.
[0097] The above results indicate that by further introducing CD47-derived peptides into the zwitterionic copolymer modified layer, the present invention can reduce the release level of TNF-α pro-inflammatory factors, thereby improving the anti-inflammatory properties and immunocompatibility of bioprosthetic valve materials.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A biomimetic composite coating modified biological valve material, characterized in that, The invention includes a biological substrate, the surface of which is sequentially modified by chemical bonding with an amino-containing cationic polymer layer, a zwitterionic copolymer layer, and a CD47-derived peptide layer. The amino-containing cationic polymer is branched polyethyleneimine; The zwitterionic copolymer is prepared by the following method: dissolving a zwitterionic monomer, an active ester monomer, an initiator, and a chain transfer agent in a solvent and performing RAFT polymerization; wherein the zwitterionic monomer is 2-methacryloyloxyethyl phosphocholine; the active ester monomer is N-hydroxysuccinimide methacrylate; the initiator is azobisisobutyronitrile; and the chain transfer agent is 4-cyano-4-(thiobenzoyl)valerate.
2. The biomimetic composite coating modified bio-valve material according to claim 1, characterized in that, The biological substrate is decellularized bovine or porcine pericardium.
3. The biomimetic composite coating modified bio-valve material according to claim 1, characterized in that, The amino acid sequence of the CD47-derived peptide is GNYTCEVTELTREGETIIELK-NH2.
4. The method for preparing the biomimetic composite coating modified biological valve material according to any one of claims 1-3, characterized in that, The steps are as follows: (1) The biological substrate is pretreated to obtain a pretreated biological substrate; (2) The pretreated biological substrate obtained in step (1) is immersed in an amino-containing cationic polymer solution and an activator is added to carry out amination modification to obtain an amino-containing cationic polymer layer. (3) Immerse in zwitterionic copolymer solution and perform covalent grafting to obtain zwitterionic copolymer layer; (4) Immerse in CD47-derived peptide solution for functionalization coupling to obtain CD47-derived peptide layer; (5) Immerse in a solution containing active ester compounds and perform surface residual active amino sealing treatment to obtain a biomimetic composite coating modified biovalve material.
5. The method for preparing the biomimetic composite coating modified biological valve material according to claim 4, characterized in that, In step (1), the biological substrate is decellularized and cross-linked with glutaraldehyde to complete the pretreatment.
6. The method for preparing the biomimetic composite coating modified biological valve material according to claim 4, characterized in that, In step (2), the activator is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide.
7. The method for preparing the biomimetic composite coating modified biological valve material according to claim 4, characterized in that, In step (5), the active ester compound is acetic acid-N-succinimide ester.
8. The application of the biomimetic composite coating modified biological valve material according to any one of claims 1-3 in the preparation of biological valves.